An integrated analysis of factors affecting consumers' purchase intention toward batik: a comparative study between Indonesia and Malaysia. (10th December 2021) - Keni, Keni; R., Lerbin R. Aritonang; Pamungkas, Ary Satria; Wilson, Nicholas
This paper was written to understand which factors play a significant and important role in determining consumers' intention to purchase batik in Indonesia and Malaysia. This study implements the survey method, with questionnaires as the tools which had been used to collect all of the data required in this study. A total of 208 samples were collected in Indonesia, while a total of 204 samples were collected in Malaysia. All the respondents were those who have bought, used, or purchased batik for the past two years. After collecting all the data required in this study, the data were then analysed using PLS-SEM method in order to understand and gather some important information regarding the relationships between variables assessed in this study. After analysing all data, it can be concluded that in Indonesia, only perceived value has a direct and significant impact on purchase intention, while in Malaysia, only perceived quality has a significant and positive impact toward purchase intention through trust.